Prevalência e fatores associados à infecção por Toxoplasma gondii e Sporothrix spp. em gatos domésticos na Paraíba - Fernandes, Ana Letícia Pereira (2023)
One health is the mutual and inseparable relationship between human, animal and environment health, being necessary for the survival of the ecosystem and its imbalance generates an increase in zoonotic diseases. Rapid environmental, cultural and social changes have generated greater proximity between humans and animals and in some cases this contact becomes so intimate that animals are perceived as family members. Notably, during the COVID-19 pandemic, social distancing between people was recommended, as a result of which individuals spent more time at home in contact with their pets, which became a primary support. This coexistence brought several benefits to the mental health and well-being of both, however the coexistence of companion animals in close physical contact with their guardians can predispose to the transmission of zoonoses. Sporotrichosis and toxoplasmosis are neglected emerging zoonoses and are growing exponentially in Brazil. Felines are common hosts and play a crucial role in the epidemiology of these conditions since they are the only species that can excrete environmentally resistant T. gondii oocysts in the feces and the species most affected by S. brasiliensis. Thus, the work aims to characterize the epidemiological situation of these diseases in domestic cats in Paraíba. In João Pessoa, 267 blood samples were collected from domestic cats and the indirect immunofluorescence reaction (IFAT) was performed for diagnosis. The cut-off point adopted for seropositivity was 1:16. The prevalence of anti-T. gondii in cats was 17.22% (46/267; 95%CI= [14.1 – 33.2]). A factor associated with infection was found in relation to age (over 60 months; PR=5,744 - CI=[1,368-24,121] - P= 0.017) and region where they live (urban area, PR=8,515 - CI=[4,424-16,390 ] - P=<0.0001). For sporotrichosis, 239 blood samples from cats from João Pessoa and Sousa 76 were used. All animals came from veterinary clinics in João Pessoa and from the Veterinary Hospital of the Federal Institute of Education, Science and Technology of Paraíba, campus Sousa-PB. To perform the diagnosis, ELISA (Enzyme-Linked Immunosorbent Assay) was performed in duplicate. The exoantigen used in the study was prepared from the mycelial form of Sporothrix brasiliensis CFP 817. The cutoff point for serum to exoantigen was defined as the mean of negative controls plus 3 times the standard deviation of negative controls. Thus, an overall prevalence of 42.22% was found (133/315 CI 95%= [36.8-47.7]). The factor associated with Sporothrix spp infection in João Pessoa was age, where 12-month- old cats are 4,785x more likely to be positive and animals aged between 13 and 60 months are 2,722x more likely to have anti- Sporothrix brasiliensis antibodies. There were no factors associated with infection in animals from the sertão of Paraíba. It is concluded that the seroprevalence of T. gondii infection is considered low. However, the characteristics presented in this study for sporotrichosis suggest an epidemic. Therefore, it is crucial to reinforce information about health education, prophylaxis, monitoring of the epidemiological profile of the animal population, zoonoses control program and feline castration.